Sei whales (Balaenoptera borealis): Photo identification and habitat preferences of a migrant traveller in São Miguel, Azores - Leal, Margarida de Sousa (2021)
The sei whale (Balaenoptera borealis) is a migratory baleen whale that undertakes migrations between breeding grounds in low latitudes to feeding areas in high latitudes. Along its migration path, it was observed passing through Azores. This study uses opportunistic data from a whale watching company located in São Miguel Island, Futurismo Azores Adventures, between 2008 and 2020. The aim of the work is to understand the distribution of sei whales around São Miguel, assessing their movement patterns through photo-identification and their habitat preferences with Generalized Additive Models. As secondary aims, temporal distribution and residence time were assessed. The habitat preferences were studied by performing three models considering (1) all sightings during the study period (2008-2020), (2) sightings from 2008 to 2014, and (3) sightings from 2015 to 2020. Sei whales’ sightings were more frequent in spring and summer, with a dominant northwest travelling direction, which agrees with the expected northward migration to the feeding grounds in that season. Along the study period, we suggest they are passing through the Azores later in the season. We could identify eighty-seven individuals with three re-sightings in São Miguel, with short times of permanence (max. registered of one month) in the study area, suggesting predominant travelling behaviour (migrating). Sea surface temperature and gradient were significant variables for the three models considered, although with different influences shown in the smoother graphs. As general choices along the study period, sei whales prefer temperatures lower than 20ºC, low values of temperature gradient (< 0.0005 ºC/km), high values of chlorophyll-a (> 0.70 mg/m3) and depth higher than 500m. The model 1 presented a lower AUC (Area Under the Curve) than models 2 and 3, that suggest sei whales prefer different environmental conditions along the time. In this study, we provide a thorough understanding of sei whale occurrence in São Miguel, Azores, essential to ...